Investigating the patterns and determinants of seasonal variation in vitamin D status in Australian adults: the Seasonal D Cohort Study. (December 2016) - King, Laura; Dear, Keith; Harrison, Simone; van der Mei, Ingrid; Brodie, Alison; Kimlin, Michael; Lucas, Robyn
Abstract Background Vitamin D status generally varies seasonally with changing solar UVB radiation, time in the sun, amount of skin exposed, and, possibly, diet. The Seasonal D Study was designed to quantify the amplitude and phase of seasonal variation in the serum concentration of 25-hydroxyvitamin D, (25OH)D)) and identify the determinants of the amplitude and phase and those of inter-individual variability in seasonal pattern. Methods The Seasonal D Study collected data 2-monthly for 12 months, including demographics, personal sun exposure using a diary and polysulphone dosimeters over 7 days, and blood for serum 25(OH)D concentration. The study recruited 333 adults aged 18–79 years living in Canberra (35°S, n  = 168) and Brisbane (27°South, n  = 165), Australia. Discussion We report the study design and cohort description for the Seasonal D Study. The study has collected a wealth of data to examine inter- and intra-individual seasonal variation in vitamin D status and serum 25(OH)D levels in Australian adults.